Effect of comorbidities on long‐term outcomes of colorectal cancer patients. (16th February 2022) - Quintana, José M.; Anton‐Ladislao, Ane; Lázaro, Santiago; Gonzalez, Nerea; Bare, Marisa; Fernandez‐de‐Larrea, Nerea; Redondo, Maximino; Escobar, Antonio; Sarasqueta, Cristina; Garcia‐Gutierrez, Susana; Aguirre, Urko; ,
Abstract: Objective: The objective of this work is to evaluate the association of comorbidities with various outcomes in patients diagnosed with colon or rectal cancer. Methods: We conducted a prospective cohort study of patients diagnosed with colon or rectal cancer who underwent surgery. Data were gathered on sociodemographic, clinical characteristics, disease course, and the EuroQol EQ‐5D and EORTC QLQ‐C30 scores, up to 5 years after surgery. The main outcomes of the study were mortality, complications, readmissions, reoperations, and changes in PROMs up to 5 years. Multivariable multilevel logistic regression models were used in the analyses. Results: Mortality at some point during the 5‐year follow‐up was related to cardiocerebrovascular, hemiplegia and/or stroke, chronic obstructive pulmonary disease (COPD), diabetes, cancer, and dementia. Similarly, complications were related to cardiovascular disease, COPD, diabetes, hepatitis, hepatic or renal pathologies, and dementia; readmissions to cardiovascular disease, COPD, and hepatic pathologies; and reoperations to cerebrovascular and diabetes. Finally, changes in EQ‐5D scores at some point during follow‐up were related to cardiocerebrovascular disease, COPD, diabetes, pre‐existing cancer, hepatic and gastrointestinal pathologies, and changes in EORTC QLQ‐C30 scores to cardiovascular disease, COPD, diabetes, and hepatic and gastrointestinal pathologies. Conclusions: Optimising the management of the comorbidities most strongly related to adverse outcomes may help to reduce those events in these patients.